An international collaboration studying the physiological and anatomical cerebral effects of carbon dioxide during head-down tilt bed rest: the SPACECOT study - Marshall-Goebel, Karina; Mulder, Edwin; Donoviel, Dorit; Strangman, Gary; Suarez, Jose I; Venkatasubba Rao, Chethan; Frings-Meuthen, Petra; Limper, Ulrich; Rittweger, Jörn; Bershad, Eric M (Journal of applied physiology (1985), 2017)
Exposure to the microgravity environment results in various adaptive and maladaptive physiological changes in the human body, with notable ophthalmic abnormalities developing during 6-mo missions on the International Space Station (ISS). These findings have led to the hypothesis that the loss of gravity induces a cephalad fluid shift, decreased cerebral venous outflow, and increased intracranial pressure, which may be further exacerbated by increased ambient carbon dioxide (CO ) levels on the ISS. Here we describe the SPACECOT study (studying the physiological and anatomical cerebral effects of CO during head-down tilt), a randomized, double-blind crossover design study with two conditions: 29 h of 12° head-down tilt (HDT) with ambient air and 29 h of 12° HDT with 0.5% CO The internationally collaborative SPACECOT study utilized an innovative approach to study the effects of headward fluid shifting induced by 12° HDT and increased ambient CO as well as their interaction with a focus on cerebral and ocular anatomy and physiology. Here we provide an in-depth overview of this new approach including the subjects, study design, and implementation, as well as the standardization plan for nutritional intake, environmental parameters, and bed rest procedures. A new approach for investigating the combined effects of cephalad fluid shifting and increased ambient carbon dioxide (CO ) is presented. This may be useful for studying the neuroophthalmic and cerebral effects of spaceflight where cephalad fluid shifts occur in an elevated CO environment.